2015
DOI: 10.1007/s00259-015-3062-1
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-3PRGD2 SPECT to monitor early response to neoadjuvant chemotherapy in stage II and III breast cancer

Abstract: (99m)Tc-3PRGD2 SPECT seems to be useful for determining the pathological tumor response in patients with stage II or III breast cancer undergoing NCT, especially those with the HER-2-positive subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
(51 reference statements)
1
12
0
Order By: Relevance
“…The pCR rate (13/41 31.7%) in this study was similar to that reported by previous studies [8,9]. The ΔT/B 1 of primary tumors showed a ROC-AUC (0.827) which was slightly lower than in a previous study (0.89) [23]. However, both that study and the present study found that the ΔT/B ratios for breast tumors in pCR group were higher than non-pCR group.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The pCR rate (13/41 31.7%) in this study was similar to that reported by previous studies [8,9]. The ΔT/B 1 of primary tumors showed a ROC-AUC (0.827) which was slightly lower than in a previous study (0.89) [23]. However, both that study and the present study found that the ΔT/B ratios for breast tumors in pCR group were higher than non-pCR group.…”
Section: Discussionsupporting
confidence: 88%
“…A limitation of our study was its limited number of patients, though the number was larger than previous study with 99m Tc-3PRGD 2 imaging [23]. Further multi-center clinical studies with larger patient numbers would be informative: for example, the tumor subtype analyses and cut-off points could be given further consideration if the patient cohort size permitted in more hospital.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, there is still no appropriate imaging modality to monitor the efficacy of anti-angiogenic therapy. Research has shown that 99m Tc-3PRGD 2 can be applied to guide anti-angiogenic therapy by visualizing and quantifying the expression level of αvβ3 [18, 31]. Thus, 99m Tc-3PRGD 2 imaging has the potential to select suitable patients who could benefit from sorafenib chemotherapy and supply an objective basis for its curative effect.…”
Section: Discussionmentioning
confidence: 99%